Гепіди. Історичні відомості та археологічні реалії - Магомедов, Б.В. (Археологія, 2001)
Гепіди та готи в ранньоримський час мали спільну вельбарську культуру (любовідзька фаза). Після переселення на південь готи створили черняхівську культуру. В ареалі вельбарської (цецельська фаза) культури залишились гепіди. Археологи связывают ранний отрезок истории гепидов и готов с древностями вельбарской культуры (любовидзкая фаза). В начале позднеримского периода на юге Восточной Европы на основе вельбарской развивается черняховская культура. Исследователи признают значительную роль готов в создании черняховской культуры, но в составе вельбарской культуры на поздней (цецельской) фазе удельный вес каждого из народов остается спорным.
Гепиды начали продвижение на юг позднее, чем готы. С этим движением связывают появление вельбарских памятников «второй волны» на оставленных готами землях в Мазовии, Подлясье и на Волыни (К. Годловский, М.Б. Щукин). В середине ІІІ в. король Фастида безрезультатно пытался захватить готскую территорию. В IV в. гепиды оставались в ареале вельбарской культуры. Из письменных источников следует, что гепиды и готы в позднеримское время имели отдельные места расселения и собственных вождей. Они оставили разные археологические культуры — вельбарскую цецельской фазы (гепиды) и черняховскую (готы). Культура готов (прежде общая с гепидами) сильно изменилась. У гепидов изменения отразились лишь в переходе к поздней фазе вельбарской культуры. К последнему этапу германского заселения Волыни относится Качинский и другие клады. В то время гепиды были активными союзниками гуннов, но Волынь, по-видимому, оставалась их тыловой базой до середины V в., когда они получили возможность переселиться на средний Дунай. Archaeologists relate the early period of the history of the Gepids and Goths with the antiquities of the Wielbar culture (the Lubowidz phase). At the beginning of the Late Roman period, the Chemyakhovian culture developed in the south of West Europe on its base. Researchers recognize a substantial role of the Goths in creation of the Chemyakhovian culture, but the relative contribution of every people to the Wielbar culture on its late (Cecel) phase remains to be controversial.
The Gepids began their movement to the south later than the Goths. This movement is connected with the appearance of Wielbar sites of the «second wave» on the lands left by the Goths in Masowsze, Podlasje, and Volyn (K. Godlowsky, M. B. Shchukin). In the middle of the III century AD, the king Fastida failed to seize the Goth territory. In the IV century AD, the Gepids remained in the Wielbar culture’s area. The written sources indicate that the Gepids and Goths had separate places of settlement and own leaders in the Late Roman time. They left different archaeological cultures: the Wielbar one in the Cecel phase (Gepids) and the Chemyakhovian culture (Goths). The culture of the Goths (earlier, it was common with the Gepids) strongly changed.. As for the Gepids, changes were observed only in the transition to the late phase of the Wielbar culture. The last stage of the German settling of Volyn is related with the Kachinsk and other hoards. At that time, the Gepids were active allies of the Huns, but Volyn apparently remained their rear base till the middle of the V century AD, when they were able to resettle on the Middle Danube.